Mapping Narrations - Narrating Maps Concepts of the World in the Middle Ages and the Early Modern Period - Baumgärtner, Ingrid (Research in Medieval and Early Modern Culture, 2022)
This volume offers the author's central articles on the medieval and early modern history of cartography for the first time in English translation. A first group of essays gives an overview of medieval cartography, illustrating the methods of cartographers. Another analyzes world maps and travel accounts in relation to mapped spaces. A third examines land surveying, cartographical practices of exploration, and the production of Portolan atlases.